Effect of Technical Assistance on Professional Performance (Global Journal of Management and Business Research, 2022)
The purpose of this research was to identify the advantages of technical assistance in continuous training processes and its effects on the performance of health professionals who care for children under 3 years of age in the Growth and Development Control (CRED). The research showed that by incorporating the Technical Assistance (TA) variable, continuous training programs are more efficient, that is, when capacities are strengthened in the field of professional action. The study design was quantitative, according to its depth it is explanatory of a quasi- experimental type, aimed at identifying the causal relationship or effect of technical assistance on professional performance, comparing an experimental group and a control group. The general results show significant differences, the experimental group, reaching an average of 51.67, while the control group only reached 26.53, applying the non-parametric Mann Whitney U test: p#x2264;.01. Although continuous training generates progress in both groups, when incorporating the AT variable, a significant jump is evidenced compared to the control group, concluding that technical assistance improves the performance of the health personnel who attend to the CRED Control, strengthening and increasing their capabilities.
Keywords: technical assistance; professional performance; early childhood development; continuous training; CRED control